2021
DOI: 10.1016/j.celrep.2021.109165
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the tumor microenvironment of metastatic ovarian cancer by single-cell transcriptomics

Abstract: Highlights d Ovarian tumors separate into two groups: high T and low T cell infiltration groups d Granulysin-expressing CD4 + T cells are present in the high T infiltration cell group d MKI67-expressing plasmablasts are identified in high T cell infiltration tumors d Correlation of CD8 and Tox in this study with immunoreactive subtype in TCGA data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 65 publications
6
94
0
Order By: Relevance
“…Thus, integrated approaches of single-cell transcriptome sequencing and organoid models will provide useful insights and potential preclinical models to identify promising targets for anticancer drugs, facilitating personalized cancer therapy (Figure 2). Omentum (ovarian cancer) Druggable target High T cell infiltration in the omentum in ovarian cancer patients; increase of antitumor response; providing therapeutic targeting [52] Breast cancer…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, integrated approaches of single-cell transcriptome sequencing and organoid models will provide useful insights and potential preclinical models to identify promising targets for anticancer drugs, facilitating personalized cancer therapy (Figure 2). Omentum (ovarian cancer) Druggable target High T cell infiltration in the omentum in ovarian cancer patients; increase of antitumor response; providing therapeutic targeting [52] Breast cancer…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential that scRNA-seq identifies tumor composition, including immune cells, to provide cellular heterogeneity at single-cell resolution. An ovarian cancer research group analyzed scRNA-seq data of 9885 cells isolated from the omentum in six ovarian cancer patients [ 52 ]. As a result, nine major cell types were identified, including cancer, stromal, and immune cells, and high T cell infiltration significantly enhanced the antitumor response.…”
Section: Single-cell Sequencing-matched Cancer Treatmentmentioning
confidence: 99%
“…21 Moreover, it became clear that the immunological configurations of primary and metastatic EOC differ considerably from each other, 20 23 as well as that the degree of primary and metastatic EOC infiltration by immune cells exhibit considerable heterogeneity across patients. [24][25][26] In this setting, analytical approaches that go beyond the mere estimation of cellular density in diagnostic biopsies to include spatial localization and functional orientation of the immune compartment of metastatic EOC have identified components of the EOC immune contexture that are linked to improved disease outcome, as discussed here below. 10 27 T lymphocytes An elevated number of T lymphocytes infiltrating the tumor core or stroma has been linked to favorable prognosis in a large panel of malignancies.…”
Section: The Immune Microenvironment In Ovarian Carcinomamentioning
confidence: 99%
“…Other studies have characterized the microenvironment of ovarian tumors, focusing on their degree of infiltration by immune cells. Olalekan et al analyzed metastatic OC samples from the omentum of six patients and found cancer, stromal and immune cell types [75]. Two groups of samples were identified according to their high or low level of T cell infiltration, and their molecular characterization suggested an antitumor response in the highly infiltrated tumors.…”
Section: A Single-cell Perspective For the Study Of Oc Transcriptomicsmentioning
confidence: 99%